The Impact of an Individual’s Narcissistic Traits on Employability - Król, Małgorzata; Karczewska, Monika (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2024)
Objective: The objective of this paper is to identify narcissistic traits that may have an impact on an individual’s employability and to determine the nature of the influence of these traits on employability. Research Design & Methods: During the first stage, based on a critical literature review, narcissistic traits were identified and a 20-item catalogue of traits affecting an individual’s employability was created. During the second, a diagnostic survey was conducted to determine whether the narcissistic traits in the catalogue have an impact on employability, what is the direction of influence of individual narcissistic traits on employability, and whether the nature of the influence of these traits on employability varies by type. The research sample was purposive and random. 198 respondents participated in the survey. Findings: The obtained results confirmed that the proposed trait catalogue for studying the impact of narcissistic traits on employability can be considered as reliable. 13 narcissistic traits were found to weaken initial and internal employability, while 8 traits were found to weaken external employability. The trait that most significantly weakens employability is displaying a demanding attitude, while the most strengthening trait is a strong belief in the possibility of professional success. Assessments concerning the impact of narcissistic traits on initial and internal employability were similar. There were differences between assessing the nature of the impact on initial and internal employability and on external employability. Implications / Recommendations: The studies confirmed that most narcissistic traits weaken employability, while some strengthen it. It was also found that the nature of the impact of narcissistic traits may vary by type of employability. Contribution: The study showed how individual narcissistic traits affect employability. Also indicating the differences in assessing narcissistic traits in the context of initial, internal, and external employability. These findings may be useful in shaping individual employability.